Post-Translational Regulations of Foxp3 in Treg Cells and Their Therapeutic Applications - Dong, Yi; Yang, Cuiping; Pan, Fan (Frontiers in Immunology, 2021)
Regulatory T (Treg) cells are indispensable for immune homeostasis due to their roles in peripheral tolerance. As the master transcription factor of Treg cells, Forkhead box P3 (Foxp3) strongly regulates Treg function and plasticity. Because of this, a lot of efforts have been made to elucidate the mechanisms that regulate Foxp3 and its co-regulators, which will not only provide more understanding to Treg cells, but also uncover more targets for clinical applications such as autoimmune diseases, organ transplantation, and tumor therapies. Recently, many studies have shown that post-translational regulations of Foxp3, including acetylation, phosphorylation, glycosylation, methylation, ubiquitination, and others, are important for Foxp3 function and plasticity. Additionally, some of these targets have suggested great therapeutic values. In this review, we will focus mostly on emerging evidence of post-translational regulations of Foxp3 in Treg cells and their therapeutic applications.